PERAN INSTITUTIONAL REPOSITORY DALAM KOMUNIKASI ILMIAH DI UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Latif, Nur Hasyim (Association of Indonesian Library and Information Professionals, 2019)
The rapid development of institutional repositories has become a concern among university scientists. The library as an information center that collects managing and disseminating various academic works through IR provides a good impact on the development of education in universities. This study aims to describe the role of institutional repositories of the Muhammadiyah University of Yogyakarta as a means of scientific communication in the implementation of learning. The approach that the researchers did was qualitative including literature review, observation, and documentation. Data analysis used descriptive analysis. The results showed that the role of Institutional Repository in scientific communication at the University of Muhammadiyah Yogyakarta included four components, namely scientists, publishers, library, and students connected in one channel through library information literacy. However, it is still necessary to make more proactive efforts for scientists and libraries in developing this scientific communication. IR plays a vital role in the learning process in higher education to achieve higher education goals with Law No. 12 of 2012.